Everybody cooks rice - Dooley, Norah; Thornton, Peter, 1956- (Minneapolis : Carolrhoda Books, 1991)
A child is sent to find a younger brother at dinnertime and is introduced to a variety of cultures through encountering the many different ways rice is prepared at the different households visited.
Booklist
4.4
3-6
Keywords: Cookery (Rice) -- Juvenile literature; Cookery -- Rice; Cookery -- Rice